Surveillance-based evidence: elimination of schistosomiasis as a public health problem in the Peoples' Republic of China - Jing Xu; Shi-Zhu Li; Li-Juan Zhang; Robert Bergquist; Hui Dang; Qiang Wang; Shan Lv; Tian-Ping Wang; Dan-Dan Lin; Jian-Bing Liu; Guang-Hui Ren; Kun Yang; et al. (BMC, 2020)
Abstract Background A steady progress on schistosomiasis control in the Peoples' Republic of China (P.R. China) was achieved and broadened into the twelve-year medium and long term national plan (MLNP) which marled the implementation of an integrated control strategy across all endemic areas in P.R. China in 2004. To understand the endemic trends of schistosomiasis to assess the effectiveness of an integrated strategy, we conducted an analysis of schistosomiasis surveillance data spanned from 2005 to 2015. Methods The schistosomiasis sentinel surveillance data from sentinel sites were collected and analyzed from 2005 to 2015. In these sentinel sites, residents aged 6 years or above were screened annually by indirect hemagglutination assay (IHA), while only antibody positives were followed by stool examination either Kato-katz method (KK) and/or hatching technique (HT). Domestic animals raised in sentinel sites were examined by HT for confirming the infection of schistosomes. Snail investigation was conducted each year through systematic sampling method combined with environmental sampling method. The snails collected from field were tested by microscopic dissection method. The infection rates of schistosomes in residents, domestic animals and snails, as well as the indicators reflecting the snails' distribution were calculated and analyzed. ANOVA analysis was used to examine the changes of the number of eggs per gram feces in population and Chi-square test was used to examine any change in proportions among groups. Results A total of 148 902 residents from sentinel sites attended this study and 631 676 blood samples were examined by IHA test during the 11 covered years. The annual average antibody positive rates presented a significant decrease trends, from 17.48% (95% CI: 17.20-17.75%) in 2005 to 5.93% (95% CI: 5.71-6.15%) (χ 2 = 8890.47, P < 0.001) in 2015. During 2005-2015, the average infection rate of schistosomes in residents declined from 2.07% (95% CI: 1.96-2.17%) to 0.13% (95% CI: 0.09-0.16%), accompanied by significant decrease of infection intensity in population. In 2015, the stool positives were only found in farmers, fishermen and boatmen with infection rate of 0.16% (95% CI: 0.11-0.20%), 0.17% (95% CI: 0-0.50%) respectively. The infection rate of schistosomes in domestic animals dropped from 9.42% (538/5711, 95% CI: 8.66-10.18%) to 0.08% (2/2360, 95% CI: 0-0.20%) from 2005 to 2015. Infections were found in eight species of domestic animals at the beginning of surveillance while only two cattle were infected in 2015. Totally 98 ha of new snail habitats were found, while 94.90% (93/98) distributed in lake and marshland regions. The percentage of frames with snails decreased from 16.96% (56 884/33 5391, 95% CI: 16.83-17.09%) in 2005 to 4.28% (18 121/423 755, 95% CI: 4.22-4.34%) in 2014, with a slightly increase in 2015. Meanwhile, the infection rate of schistosomes in snails was decreased from 0.26% (663/256 531, 95% CI: 0.24-0.28%) to zero during 2005-2015. Conclusions The infection rate of schistosomes declined significantly, providing evidence that the goal of the MLNP was achieved. Elimination of schistosomiasis as a public health problem defined as WHO was also reached in P.R. China nationwide. Surveillance-response system should be improved and strengthened to realize the final goal of schistosomiasis elimination.